Optimal internal “shadow” taxation on condition of a firm external economic activity - Гончаренко, А. В.; Запорожченко, О. А. (Proceedings of National Aviation University (archive), 2013)
In the given work, it is made an attempt to build a simplified mathematical model of financial functioning of an enterprise which leads its own internal economic activity in conditions of two parallel existing economies: “light”, which is being taxed officially by the state establishments, and “shadow”, controlled by the corruption structures by their own schemes of taxation; as well as, external economic activity, at the given consideration without the “shadow” component. The suggested model allows researching the optimal control of the financial-economic process development by the each of the “players”: the firm, internal state official and “shadow”, as well as the external state structures. The application of the subjective entropy extremizaton principle allows obtaining the canonical distributions of the “players’” individual preferences which demonstrate the presence and intensity of the optimal values of the continuous controlling parameters. Conducted numerical experiments have been illustrated with the corresponding diagrams